Transfusion trigger after operations in high cardiac risk patients (TOP) trial protocol. Protocol for a multicenter randomized controlled transfusion strategy trial - Kougias, Panos; Mi, Zhibao; Zhan, Min; Carson, Jeffrey L.; Dosluoglu, Hasan; Nelson, Peter; Sarosi, George A.; Arya, Shipra; Norman, L. Erin; Sharath, Sherene; Scrymgeour, Alexandra; Ollison, Jade; et al. (Contemporary clinical trials, 2023)
There is substantial uncertainty regarding the effects of restrictive postoperative transfusion among patients who have underlying cardiovascular disease. The TOP Trial's objective is to compare adverse outcomes between liberal and restrictive transfusion strategies in patients undergoing vascular and general surgery operations, and with a high risk of postoperative cardiac events. A two-arm, single-blinded, randomized controlled superiority trial will be used across 15 Veterans Affairs hospitals with expected enrollment of 1520 participants. Postoperative transfusions in the liberal arm commence when Hb is <10 g/ dL and continue until Hb is greater than or equal to 10 g/dL. In the restrictive arm, transfusions begin when Hb is <7 g/dL and continue until Hb is greater than or equal to 7 g/dL. Study duration is estimated to be 5 years including a 3-month start-up period and 4 years of recruitment. Each randomized participant will be followed for 90 days after randomization with a mortality assessment at 1 year. The primary outcome is a composite endpoint of all-cause mortality, myocardial infarction (MI), coronary revascularization, acute renal failure, or stroke occurring up to 90-days after randomization. Events rates will be compared between restrictive and liberal transfusion groups. The TOP Trial is uniquely positioned to provide high quality evidence comparing transfusion strategies among patients with high cardiac risk. Results will clarify the effect of postoperative transfusion strategies on adverse outcomes and inform postoperative management algorithms. TRIAL REGISTRATION: http://clinicaltrials.gov identifier: NCT03229941